Effects of gelatin and glutaraldehyde concentrations on characteristics of Cantigi (Vaccinium varingiaefolium Miq.) extract loaded gelatin nanoparticles as antioxidant - Kosasih Kosasih; Wahono Sumaryono; Diky Mudhakir; Agus Supriyono; Yulius Evan Christian; Ruth Debora (Journal of halal product and research (JPHR), 2021)
Cantigi is an endemic plant of sub-alpine area of Mount Tangkuban Parahu in Bandung, Indonesia. Previous study showed ethanol extract of young red leaves had antioxidant activity, however no information on this activity if changed into nanoparticles. The purpose of this study was to determine the effects of gelatin and glutaraldehyde concentrations on the characteristics of Cantigi extract loaded gelatin nanoparticles and to evaluate the antioxidant activity of nanoparticles. Cantigi leaves were extracted by maceration using n-hexane, ethyl acetate, and ethanol 96%. The ethanol extract was dried, made into nanoparticles by varying gelatin (0.1; 0.2; and 0.3 g) and glutaraldehyde (0.1; 0.2; and 0.3 mL) amounts, and conducted at 500 rpm and 40 °C for 3 hours. Nanoparticles were evaluated for particle size, zeta potential, morphology, and antioxidant activity. Nanoparticles with glutaraldehyde amount variation had particle sizes (PS) of 105.9±26.2; 37.1±8.7; and 32.5±7.4 nm; polydispersity indeces (PI) of 0.508; 0.717; and 0.563; zeta potential values (ZPV) of 0.55; 0.89; and 0.78 mV; and antioxidant activities (IC50) of 56.15±0.16; 53.67±0.10; and 51.57±0.39 ppm, respectively. Then, nanoparticles with gelatin amounts variation had PS of 22.5±5.1; 37.1±8.7; and 83.3±21 nm; PI of 0.604; 0.717; 0.326; ZPV of 1.27; 0.89; 0.18 mV; and antioxidant activities of 51.58±0.19; 53.67±0.12; and 55.46±0.04 ppm, respectively. Nanoparticle morphology was spherical. Cantigi leaf extract can be made into gelatin nanoparticles; the smaller the concentration of the polymer used and higher the concentration of the glutaraldehyde, the smaller the resulted particle size and increased antioxidant activity. Antioxidant activities of nanoparticles was lower than those of the extract (IC50 16.84±0.30 ppm).